Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsbiomaterials.1c01140
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal SDF-1 Alpha Delivery in Nanocomposite Hydrogels Promotes Macrophage Phenotype Changes and Skin Tissue Regeneration

Abstract: Skin regeneration in chronic wounds is often delayed due to persistent inflammation induced by underlying conditions such as diabetes. This effect is mediated, in part, by macrophages present in the wound, which can be stimulated to adopt either pro- or anti-inflammatory phenotypes depending on the status of the local microenvironment. In this work, the prohealing chemokine stromal cell-derived factor-1 alpha (SDF-1α) is controllably released from a hydrogel-based biomaterial to promote skin tissue regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…To protect SDF-1α, Yu et al (2020) prepared a kind of nanogel-loaded liposome that stimulates the recruitment of bone marrow mesenchymal stem cells, secretes cytokines, regulates the phenotypes of other effector cells and effectively promotes wound closure and tissue regeneration. Other studies have found that these nanocomposite hydrogels containing SDF-1α could influence macrophage phenotype and promote skin tissue regeneration in diabetic mice ( Yu J. R. et al, 2021 ).…”
Section: Application Of a Nanocomposite Hydrogel Delivery System To D...mentioning
confidence: 96%
“…To protect SDF-1α, Yu et al (2020) prepared a kind of nanogel-loaded liposome that stimulates the recruitment of bone marrow mesenchymal stem cells, secretes cytokines, regulates the phenotypes of other effector cells and effectively promotes wound closure and tissue regeneration. Other studies have found that these nanocomposite hydrogels containing SDF-1α could influence macrophage phenotype and promote skin tissue regeneration in diabetic mice ( Yu J. R. et al, 2021 ).…”
Section: Application Of a Nanocomposite Hydrogel Delivery System To D...mentioning
confidence: 96%
“…Novel blood vessels produce sufficient blood supply and afford a favorable microenvironment for the proliferation and migration of dermal and epidermal cells. 50,51 To further investigate the mechanism of skin-wound healing, the inflammation condition and angiogenesis were evaluated by CD31 immunohistochemical staining. As shown in Fig.…”
Section: Histology and Immunohistochemistry Evaluationmentioning
confidence: 99%
“…49 Regarding the antibacterial activity of chitosan in dressings for skin, some studies have evidenced this character in their biodressing formulations and note that this property can reduce wound site infection. 16,17,54 In this sense, the study by Abbas et al, 55 evaluated antibacterial dressings for burn wound healing using chitosan/poly(vinyl alcohol) CS/PVA membranes containing curcumin in different concentrations, with the latter used pure and associated with zinc oxide. The wound healing potential was tested in rabbits.…”
Section: Use Of Chitosan Matrix In Dressings For Burned Skinmentioning
confidence: 99%
“…The skin structure is composed of three distinct layers: epidermis, dermis, and hypodermis (Figure 1). The epidermis is histologically composed of a keratinized stratified squamous epithelium, 17 which constitutes a very effective physical barrier to the penetration of microorganisms and eventual toxins while also conserving the body's moisture and nutrient content 18–20 . Its outermost layer, the stratum corneum, consists of the last stage of differentiation of keratinocytes (characteristic epidermis cells), being composed of a layer of dead cells whose cytoplasm is completely filled with keratin fibrils amidst lipid bilayers, this layer is constantly being eliminated by the natural shedding of this tissue that undergoes constant renewal in the human body 21 …”
Section: Skinmentioning
confidence: 99%